الصراع على السلطة في مسرحية رأس المملوك جابي - مصار حنان (My University, 2024)
Abstract This study aims to reveal the most prominent motives for returning to heritage and the most important heritage sources for Wannous Theater and to reveal the dimensions of the storyteller and the types of narrator in his theatre, and thus a comprehensive look at the role that heritage plays in reviving the history of nations and proving existence, belonging and preserving identity, as it is the bridge linking our past and our present and through it. Nations can address their current issues, in addition to examining the traditional forms in the Wannous Theater and the extent of its inspiration for heritage, revealing the function of the narrator and storyteller in the Saadallah Wannous Theater, and identifying the dimensions of the storyteller and the types of narrator in the Wannous Theater. This study was divided into two chapters. The first chapter dealt with the concept of theater and the study of Brecht’s influence on Saadallah Wannous’s theatre, leading to the foundation of theater on the authority of Saadallah Wannous. After that, the study of the concept of conflict and the concept of conflict was addressed. The causes of conflict were also studied, and its importance is the concept of authority. Finally, the concept of authority through studying its definition and types of traditional, psychological, and legitimacy As for the second chapter, it was devoted to talking about a reading of the content of the play Ras al-Mamluk Jaber and the manifestations of the conflict in the play and its forms over power in the play, leading to alienation and breaking the illusion in the play. After that, we moved on to studying the artistic phenomena in the play from the styles of storytelling. Through the study, we concluded that Wannous was able to mix authenticity and modernity by drawing inspiration from heritage and employing popular traditional forms and formulating them according to Western standards represented by Westernization and breaking illusions. Thus, Wannous was able to establish the first structure and establish an authentic Arab theater and remove it from the circle of tradition that has been surrounded by it since ancient times. In the end, it should be established so that theater remains the best educational and purposeful media tool between the author and the audience, and one of the biggest factors in the renaissance in the past and in the present. ----------------------- تهدف هذه الدراسة إلى الكشف عن أبرز دوافع العودة إلى التراث وأهم المصادر التراثية لمسرح ونوس والكشف عن أبعاد الحكواتي وأنماط الراوي في مسرحه، وبالتالي نظرة شاملة إلى الدور الذي يلعبه التراث في إحياء تاريخ الأمم واثبات الوجود والانتماء والمحافظة على الهوية فهو الجسر الرابط بين ماضينا وحاضرنا وبواسطته تستطيع الأمم أن تعالج قضاياها الراهنة، فضلا على الوقوف عند الأشكال التراثية في مسرح ونوس ومدى استلهامه للتراث، الكشف عن وظيفة الراوي والحكواتي في مسرح سعد الله ونوس، والتعرف على أبعاد الحكواتي وأنماط الراوي في مسرح ونوس. وقد قسمت هذه الدراسة إلى فصلين تناول الفصل الأول فهوم المسرح ودراسة أثر بريخت في مسرح سعد الله ونوس، وصولا إلى تيسسيست المسرح عن سعد الله ونوس، بعدها تم التطرق إلى دراسة مفهوم الصراع ومفهوم النزاع، كما تم دراسة أسباب الصراع، وأهميته مفهوم السلطة، ليأتي في أخير مفهوم السلطة من خلال دراسة تعريفها وأنواعها من التقليدية، والنفسية، والشرعية أما الفصل الثاني فقد تخصص بالحديث عن قراءة في مضمون مسرحية رأس المملوك جابر وتجليات الصراع في المسرحية واشكاله على السلطة في المسرحية، وصولا إلى التغريب وكسر الايهام في المسرحية بعدها تم الإنتقال إلى دراسة الظواهر الفنية في المسرحية من أنماط القص وتوصلنا من خلال الدراسة إلى أن ونوس استطاع أن يمزج بين الأصالة والمعاصرة باستلهامه للتراث وتوظيفه للأشكال التراثية الشعبية وصياغتها وفق معايير غربية تمثلت في التغريب وكسر الايهام وبذلك استطاع ونوس أن يضع البنية الأولى وأن يؤسس لمسرح عربي أصيل وأن يخرجه من دائرة التقليد التي طوق بها منذ القديم وأن يؤسس ليبقى المسرح في الأخير أفضل وسيلة إعلامية تثقيفية هادفة بين المؤلف والجمهور وأحد أكبر عوامل النهضة قديما وحديثا. ----------------------------- Résumé Cette étude vise à révéler les motivations les plus marquantes du retour au patrimoine et les sources patrimoniales les plus importantes pour le Théâtre Wannous et à révéler les dimensions du conteur et les types de narrateur dans son théâtre, et ainsi un regard global sur le rôle que joue le patrimoine. joue pour faire revivre l'histoire des nations et prouver l'existence, l'appartenance et la préservation de l'identité, car c'est le pont qui relie notre passé et notre présent et à travers lui les nations peuvent aborder leurs problèmes actuels, en plus d'examiner les formes traditionnelles dans le Théâtre Wannous et. l'étendue de son inspiration pour le patrimoine, révélant la fonction du narrateur et du conteur au Théâtre Saadallah Wannous, et identifiant les dimensions du conteur et les types de narrateur au Théâtre Wannous. Cette étude a été divisée en deux chapitres. Le premier chapitre traitait du concept de théâtre et de l'étude de l'influence de Brecht sur le théâtre de Saadallah Wannous, conduisant à la fondation du théâtre sous l'autorité de Saadallah Wannous. Ensuite, l'étude du concept de théâtre. Le conflit et le concept de conflit ont été abordés. Les causes du conflit ont également été étudiées, et son importance est le concept d'autorité. Enfin, le concept d'autorité en étudiant sa définition et ses types de légitimité traditionnelle, psychologique et. Quant au deuxième chapitre, il était consacré à la lecture du contenu de la pièce Ras al-Mamluk Jaber et aux manifestations du conflit dans la pièce et à ses formes de pouvoir dans la pièce, conduisant à l'aliénation et brisant l'illusion. dans la pièce. Après cela, nous sommes passés à l'étude des phénomènes artistiques de la pièce à partir des styles de narration. Grâce à l'étude, nous avons conclu que Wannous était capable de combiner authenticité et modernité en s'inspirant du patrimoine et en employant des formes traditionnelles populaires et en les formulant selon les normes occidentales représentées dans l'occidentalisation et en brisant les illusions. Ainsi, Wannous a pu établir la première structure et. établir un théâtre arabe authentique et le sortir du cercle de la tradition qui l'entoure depuis l'Antiquité et établir le théâtre de telle sorte qu'en fin de compte, il reste le meilleur outil médiatique éducatif et utile entre l'auteur et le public, et l’un des facteurs les plus importants de la renaissance d’hier et d’aujourd’hui
Keywords: Saadallah Wannous; theatre; conflict; power; Ras al-Mamluk Jaber; Westernisation; the story(Modifié)Restaurer la traduction d'origine; سعد الله ونوس، المسرح، الصراع، السلطة، رأس المملوك جابر، التغريب، القصة; théâtre; conflit; pouvoir; occidentalisation; récit